Insight into the issue of underutilised parks: what triggers the process of place attachment?. Issue 2 (4th May 2021) - Moulay, Amine; Ujang, Norsidah
ABSTRACT: Public spaces that include neighbourhood parks have a significant function in supporting and enhancing social life. They facilitate interaction between people and their environment, thus improving social connectedness and promoting residents' well-being. However, there were raising concerns on the under-utilisation of parks over the years where it has become a crucial part of the global urban agenda. To this end, comprehending place attachment is crucial to enhance the meaning, functions, and attraction of places. This qualitative study attempts to provide thorough contextual insights on the attachment process from park users' perspective. A sample of 28 park users was selected purposively within the neighbourhood of Precinct 9, Putrajaya, Malaysia. In-depth semi-structured interviews were performed face to face and later transcribed verbatim, then analysed through an Interpretative Phenomenological Analysis approach. Two themes and five sub-themes emerged from the interviews. First is the park's attachment process, including emotional attachment, park's meaning, and functional attachment. Second is the cognitive aspect of park use, including attitudes and beliefs related to parks. Findings revealed that the process of park's attachment is interrelated while the functional attachment is the key concept to attract residents to the neighbourhood park and the trigger of the whole attachment process.